INSTRUMEN EVALUASI PROGRAM PENDIDIKAN DI MTS LAB. UINSU, MEDAN - Nisa Miranda (JGK (Jurnal Guru Kita), 2022)
Abstract : Training is seen as the primary method for dealing with different social issues in many countries, and for certain issues, public government assistance rests on the shoulders of schools and colleges. The implementation of the instructive program must be seen from a different perspective. This point of view combines public authorities as strategy creators, clients and regions as teachers in proportion to program continuity. The evaluation, called program assessment, is expected to be able to decide the outcome of the instructive program being run. This is often referred to as an educational program assessment, basically because it assesses an educational program. Ranking empowers students to effectively take part in long-term learning, educators to work more on the nature of the educational experience, and schools to work more on the tools and nature of board schools. However, relying solely on student implementation and educational evaluation to assess the progress of a learning program is not enough. Evaluation is a movement to collect valuable data for an independent direction and is used as a proportion of the extent to which a goal can be achieved. Program assessment is a technique for deciding project implementation by comparing the program and the specific measures or objectives achieved and the results achieved.Keywords: Program Evaluation, Instrument, EducationAbstrak : Pelatihan dipandang sebagai metode utama untuk menangani isu-isu sosial yang berbeda di banyak negara, dan untuk isu-isu tertentu, bantuan pemerintah publik berada di pundak sekolah dan perguruan tinggi. Pelaksanaan program instruktif harus terlihat menurut perspektif yang berbeda. Sudut pandang ini menggabungkan otoritas publik sebagai pencipta strategi, klien dan daerah sebagai guru sebanding dengan kelangsungan program. Evaluasi yang disebut penilaian program diharapkan dapat memutuskan hasil dari program instruktif yang dijalankan. Hal ini sering disebut sebagai penilaian program edukatif, pada dasarnya karena menilai sebuah program edukatif. Peringkat memberdayakan siswa untuk secara efektif mengambil bagian dalam pembelajaran jangka panjang, pendidik untuk lebih bekerja pada sifat pengalaman pendidikan, dan sekolah untuk lebih bekerja pada peralatan dan sifat sekolah dewan. Namun, hanya bergantung pada pelaksanaan siswa dan evaluasi pendidikan untuk menilai kemajuan program pembelajaran tidak cukup. Evaluasi adalah gerakan untuk mengumpulkan data yang berharga untuk arah independen dan digunakan sebagai proporsi sejauh mana suatu tujuan dapat dicapai. Penilaian program adalah teknik untuk memutuskan pelaksanaan proyek dengan membandingkan program dan ukuran atau tujuan tertentu yang dicapai dan hasil yang dicapai.Kata Kunci : Evaluasi Program, Instrumen, Pendidikan